The Exxon Valdez : the oil spill off the Alaskan Coast - Streissguth, Thomas, 1958- (Mankato, MN : Capstone High-Interest Books, 2003)
Describes the oil tanker Exxon Valdez, the events that led up to its disastrous oil spill in 1989, and the effects of the spill on the Alaskan environment.
Includes bibliographical references (p.31) and index.
Keywords: Exxon Valdez (Ship) -- Juvenile literature; Exxon Valdez (Ship); Oil spills -- Environmental aspects -- Alaska -- Prince William Sound Region -- Juvenile literature; Tankers -- Accidents -- Environmental aspects -- Alaska -- Prince William Sound Region -- Juvenile literature; Oil spills -- Alaska -- Prince William Sound region; Tankers -- Accidents